PENGARUH CAPITAL EXPENDITURE, CASH CONVERSION CYCLE, CASH FLOW, GROWTH OPPORTUNITY, DAN NET WORKING CAPITAL TERHADAP CASH HOLDING (STUDI EMPIRIS PADA PERUSAHAAN SUB-SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2019-2023) - Wardani, Fatimah Kusuma; Whetyningtyas, Aprilia; Mulyani, Ulva Rizky (JAB (Jurnal Akuntansi & Bisnis), 2025)
The research aims to analyze the effects of capital expenditure, cash conversion cycle, cash flow, growth opportunity, and net working capital on the cash holding. The research data used is secondary data in the form of annual reports on food and beverage sub-sector companies listed on the Indonesia Stock Exchange for 2019-2023. The sampling method used was purposive sampling. Total of samples used in this research was 125 data. The data analysis technique used is multiple linear regression analysis processed using SPSS version 29. The result of this study show that cash conversion cycle, cash flow, and net working capital have a positive quality, capital expenditure and growth opportunity have no effect on the cash holding.